The Role of National Culture in National Innovative Capacity - Handoyo, Sofik (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. Purpose of the study is to examine the relationship between national culture and the capacity of the nation to innovate. The motivation of study was driven by the differences national innovative capacity in the open access knowledge era. The total sample was involved in this study is 77 countries. Hofstede’s national culture Index and Global Competitiveness Index were used to measure national innovative capacity variable and national culture variable respectively. The study involved two control variables namely categorization of national income (low, upper low, upper medium and high) and the Human Development Index. Bivariate correlation analysis and multiple regression analysis were applied. The findings indicated that national culture classification namely individualism, long-term orientation, and indulgence were found positively and significantly related to national innovative capacity. Power distance and uncertainty avoidance national culture classification showed a negative and significant relationship with national innovative capacity. Masculinity national culture was found no relationship with national innovative capacity. Human Development Index as a control variable showed a positive and significant association with national innovative capacity. There is no indication association between income categorization and national innovative capacityKeywords:  National culture, innovative capacity, global competitiveness, power distance, uncertainty avoidance.